Chimeric (alpha-amino acid plus nucleoside-beta-amino acid)(n) peptide oligomers show sequence specific DNA/RNA recognition - Gogoi, Khirud; Kumar, Vaijayanti A. (Chemical Communications, 2008)
An alpha/beta-peptide backbone oligonucleotide comprising natural alpha-amino acids alternating with a beta-amino acid component derived from thymidine sequence specifically recognizes and binds to deoxy- and ribo-oligoadenylates in triplex mode.